THE RELATIONSHIP BETWEEN PARENTAL SUPPORT AND STUDENT DISCIPLINE CHARACTER IN 4TH GRADE INDEPENDENT CURRICULUM - Rahayu, Anisa Sri; Purnanto, Arif Wiyat; Pradana, Agrissto Bintang Aji; Sufiyati, Dwi (JPSD (Jurnal Pendidikan Sekolah Dasar), 2024)
Family involvement in education plays a crucial role in shaping a child’s character. Children with solid character contribute to preparing the next generation to face the nation’s changes. This research analyzes the relationship between parental support and the disciplined character of 4th grade class B students at MI An Nuur Cahaya Umat. The research involved 16 4th grade class B students at MI An Nuur Cahaya Umat. This research is a correlational study. The data collection method was a questionnaire, with respondents filling out a checklist and guided by a Likert scale. The data analysis technique employed in this research is the Pearson product-moment correlation analysis by Karl Pearson. The data analysis was conducted to observe the relationship between two variables, using the parametric technique with paired sample t-test, resulting in a significance level of 0.040 and Pearson correlation score of 0.518, indicating a moderate correlation. Therefore, the research findings show a significant relationship between parental support and discipline character. Thus, the conclusion drawn from this research is that higher parental support leads to the formation of stronger discipline character in students. Conversely, lower parental support correlates with lower levels of student discipline.